TEAM EFFECTIVENESS AND HR MANAGEMENT - Usheva , Mariana; Valerieva Danchova , Maria (Revista Inclusiones, 2018)
Leading issue in the functioning of every contemporary organization is the effectiveness of teams and teamwork as a key and competitive advantage. Building and developing the team does not happen “naturally” in the work process but is sequence of the deliberate efforts of everybody. The team is a live organism, where all elements act synchronically. The cooperation between separate members shall be directed towards mutual completion of the contribution of everybody as the separate individual contributes for this using their knowledge, skills and talent in the best way. Unifying the abilities of all members, directing the efforts for increase of strong features of the organization and minimizing the weak ones are fundamental for achieving the strategic goals of any organization. The main goal of this report is to identify the issues of team effectiveness and human resources management. The main research methods used in the report are content-analysis, comparative method and intuitive and systematic approach.